A crafty Christmas - Bryan, Mollie Cox, 1963- (Bryan, Mollie Cox, 1963- Cumberland Creek mystery., 2014)
"Christmas is just around the corner, and the ladies of the Cumberland Creek Scrapbook Crop are thrilled when Sheila wins the first place prize in a scrapbooking design contest: a ten-day scrapbook-themed cruise in the Caribbean. Vera and Paige decide to tag along, which should pose the perfect opportunity to learn some new techniques, mingle with fellow croppers, and get in some rest and relaxation before the chaos of Christmas. But when Sheila finds a famous crafter dead, and investigators determine she was poisoned, the luxury cruise veers toward disaster as Sheila becomes the number one suspect--or was she really the intended victim? Just as the croppers begin un-wrapping the truth, a storm strands them at sea, and they'll find it's harder than ever to survive the holidays with a killer on deck"--Page [4] of cover.